2012
DOI: 10.7307/ptt.v22i1.166
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Legislation on Road Traffic Safety

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The behaviour of traffic participants is tightly connected to enforcement; so Vaa (1995) showed that by augmenting the penalties and police controls, the number of drivers who make speeding violations decreased, which Redelmeier et al (2003) confirmed showing that a larger enforcement resulted in diminishing the risk of traffic accidents. By analyzing the methods of determining the impact of the new RTSL on the decrease of the number of traffic accidents and the number of casualties, it can be concluded that in current practice most used methods are: time-series analysis (Tominc, 2002), analysis and synthesis, mathematical statistics as well as trend assessment (Rajsman and Lisicin, 2010), but also system reliability theory (Jovanovic et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The behaviour of traffic participants is tightly connected to enforcement; so Vaa (1995) showed that by augmenting the penalties and police controls, the number of drivers who make speeding violations decreased, which Redelmeier et al (2003) confirmed showing that a larger enforcement resulted in diminishing the risk of traffic accidents. By analyzing the methods of determining the impact of the new RTSL on the decrease of the number of traffic accidents and the number of casualties, it can be concluded that in current practice most used methods are: time-series analysis (Tominc, 2002), analysis and synthesis, mathematical statistics as well as trend assessment (Rajsman and Lisicin, 2010), but also system reliability theory (Jovanovic et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%